2021
DOI: 10.1177/1470595821999075
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural issues in business ethics: A review and research agenda

Abstract: This paper reports a systematic literature review of articles published over the past 35 years on cross-cultural issues in business ethics. A screening process resulted in a final sample of 306 papers in 26 double-blind reviewed journals with an impact factor score of at least 1.0 in the field. This study uses citation analysis, systematic literature review method, and knowledge-stock analysis. This study highlights the findings from prior studies, compares and contrasts salient characteristics and provides di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 181 publications
(193 reference statements)
1
10
0
Order By: Relevance
“…This is followed by an analysis through a social identity lens considering pertinent in-group and out-group categories relevant for each country, informing behavioral response to the pandemic. This is in keeping with the view that the role of country context plays a critical role in the advancement of cross-cultural research (Ermasova, 2021), and the need to focus both within the culture and examine cross-cultural variability (Fischer and Schwartz, 2011).…”
Section: Cross-cultural Dimensions Of Difference Shaping Divergent Pandemic Responses In the Us And Indiasupporting
confidence: 69%
“…This is followed by an analysis through a social identity lens considering pertinent in-group and out-group categories relevant for each country, informing behavioral response to the pandemic. This is in keeping with the view that the role of country context plays a critical role in the advancement of cross-cultural research (Ermasova, 2021), and the need to focus both within the culture and examine cross-cultural variability (Fischer and Schwartz, 2011).…”
Section: Cross-cultural Dimensions Of Difference Shaping Divergent Pandemic Responses In the Us And Indiasupporting
confidence: 69%
“…Many authors reveal that ethical behavior perceptions are not universally shared around the world (Ardichvili et al., 2009, 2010, 2012; Bailey & Spicer, 2007; Cavico & Mujtaba, 2009; Danon‐Leva et al., 2010; Ermasova et al., 2017; Farazmand, 2017; Ford & Richardson, 1994; Jaffe et al., 2018; Jaffe & Tsimerman, 2005; McCarthy & Puffer, 2008, 2013; Morgan & Neal, 2011; Robertson et al., 2003, 2008). There are extensive studies on ethical behavior and different types of ethical organizational interventions (Burns, 2012; Calma & Davies, 2020; Carlson & Burke, 1998; Cannon, 2001; Ermasova et al., 2017; Ermasova, 2021; Jazani & Ayoobzadeh, 2012; Majluf & Navarrete, 2011; Nguyen et al, 2014; Wang & Calvano, 2015). Christie et al.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Calma and Davies (2020) found that there is a growing interest in business ethics due to pressure for businesses to engage in fair and transparent practices and “a greater sense of responsibility and accountability to customers, stakeholders and the society” (p. 8). Many scholars (Calabretta et al., 2011; Ermasova, 2021; Linuesa‐Langreo et al., 2019; Ma et al., 2012; Robertson et al., 2008; Uysal, 2010; Wang et al., 2018; Wood, 2017; Xiao & Ma, 2015) proved the differences in the ethical attitudes of people from different cultures. Gift et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations